MENGADILI SANG SAPURBA BERDASARKAN MITOS SANG SAPURBA - Muhammad Kafrawi (SURYA SENI, 2008)
The manuscript of  “Mengadili Sang Sapurba” is a process by the writer in creating a theater play. The play inspired by the reality of people’s life and poverty the of Riau using two old Malay manuscipts of  Malay History and The Tale of Hang Tuah, the writer try to “embrace” these issues. Sejarah Melayu or The Malay History describes an agreement between a king called Sang sapurba and a Malay leader named Demang Lebar Daun. This agreement gave the king power that made him stand above the law. Even when the king and his family did wrong things, his people could not stop them. Meanwhile  Hikayat Hang Tuah, represented by main character of Hang Jebat, struggled against the cruelty and arbitrariness of the ruling king. The rebellion started when Hang Jebat disagrees with an unjust death penalty delivered bythe king to his best friend Hang Tuah. Nowadays, writer sees the agreement between Sang Sapurba and Demang Lebar Daun is still hunting Malay (Riau) people. This can be seen in the current condition in Riau, where the Malays have no courage to ﬁ ght their rights. In theplay of  Mengadili Sang Sapurba, the writer feels the needs of embracing the past in order to learn and take a lesson from it.Keywords: Sang Sapurba, Hang Jebat, and Agreement.